Aboveground biomass distributions and vegetation composition changes in Louisiana's Wax Lake Delta. (5th March 2021) - Jensen, Daniel; Cavanaugh, Kyle C.; Simard, Marc; Christensen, Alexandra; Rovai, Andre; Twilley, Robert
Abstract: The Wax Lake Delta (WLD) is an actively prograding delta in the Mississippi River Delta Plain that is otherwise experiencing widespread degradation and submergence of its coastal wetlands. The WLD is actively accumulating mineral and organic sediment that increases soil surface elevation, changing emergent wetland communities as the young delta develops. There is uncertainty in how the dynamics of community composition respond to net changes in soil elevation and determine aboveground biomass and carbon storage. This study utilizes high resolution imaging spectrometer data captured on October 17, 2016, to map the delta's dominant vegetation species and wetland types. We validated this vegetation map (overall accuracy = 77.62%, Kappa = 0.72) and compared it with a published species map that used WorldView-2 data collected five years earlier on October 16, 2011. This allowed us to map changes resulting from five years of delta development to determine changes in wetland forest species ( Salix nigra ), two dominant herbaceous wetland species ( Colocasia esculenta and Polygonum punctatum ), and various grass species. Results show an increase in C. esculenta and a marginal increase in forested wetlands ( S. nigra ). C. esculenta 's expansion occurred largely from the delta island heads toward the fringes into wetland area previously occupied by P. punctatum, which saw a corresponding decline. Additionally, this study leveraged these species distributions with a published aboveground biomass (AGB) dataset to examine the dominant plant types' growth patterns across elevational gradients. We characterized variability in AGB by marsh platform elevation and across different elevational zones categorized by hydroperiod, or hydrogeomorphic zones. We found that the herbaceous plant species peak in AGB in the low intertidal zone and decrease with elevation before increasing slightly in the higher elevations, consistent with previous field-based mesocosm experiments for C. esculenta . With vegetation distributions, succession, and growth patterns in the WLD characterized, this study may inform future restoration efforts throughout the Mississippi River Delta Plain regarding the changing vegetation composition that may emerge following changes in surface elevation with sediment deposition. Graphical abstract: Image 1 Highlights: We mapped and validated vegetation species in Louisiana's Wax Lake Delta. Species extent changes over five years show an increase in Colocasia esculenta . C. esculenta grew outwards with deltaic accretion, supplanting Polygonum punctatum . Aboveground biomass for primary herbaceous species peaks in the intertidal zone. Remote sensing biomass estimates agree with experimentally derived growth rates.